MWW structure formed titanium silicalite molecular sieve as well as preparation method and application thereof

Through acid solution pretreatment and organic amine crystallization treatment, the mechanical strength and acid strength of MWW structure-formed titanium silicon molecular sieve are improved, and the problem of insufficient stability and selectivity of catalysts in the operation of industrial fixed beds in the prior art is solved, thereby achieving the goal of achieving the problem of insufficient stability and selectivity of catalysts in the operation of industrial fixed beds. Excellent catalytic properties in linear olefin epoxidation reaction.

CN119263296APending Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310818853.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to meet the demand for titanium-containing zeolite catalysts with high acid strength, high crystallinity and high mechanical strength in industrial fixed bed operation, especially in the epoxidation reaction of linear olefins. .

Method used

The original powder of Silicon-titanium molecular sieve with MWW structure was pretreated with an acid solution, followed by molding and crystallization in an organic amine solution to improve the mechanical strength and acid strength of the catalyst.

Benefits of technology

The prepared MWW structure-formed titanium silicon molecular sieve has a mechanical strength of 70N/cm-120N/cm, a relative crystallinity of 110%-130% and a high acid strength, showing excellent catalytic performance and selectivity, meeting industrial applications. Require.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263296A_ABST
    Figure CN119263296A_ABST
Patent Text Reader

Abstract

The invention provides an MWW structure formed titanium silicalite molecular sieve and a preparation method of the MWW structure formed titanium silicalite molecular sieve. The preparation method of the MWW structure molded titanium silicalite molecular sieve comprises the following steps: S1, mixing MWW structure silicon-titanium molecular sieve raw powder with an acid solution, and then performing pretreatment to obtain a pretreated product; s2, the pretreated product is subjected to forming treatment, and a formed product is obtained; and S3, mixing the molded product with an organic amine solution, and carrying out crystallization treatment. The MWW structure formed titanium silicalite molecular sieve obtained by the preparation method has high acid strength, high crystallinity and high mechanical strength, and shows excellent catalytic performance when being applied to epoxidation reaction of straight-chain olefin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and in particular relates to an MWW structure-molded titanium silicon molecular sieve with high acid strength, high crystallinity and high mechanical strength and a preparation method thereof. Background Art

[0002] Molecular sieves containing the basic structural unit of MWW are one of the typical representatives of layered molecular sieves, and their synthesis and modification methods have always attracted the interest of scientific researchers. Taking MCM-22 as an example for a specific structural analysis, its basic structural unit MWW layer plates are orderly connected by interlayer TOT bonds to form a three-dimensional MWW structure, which contains two sets of independent pore systems: one set is a two-dimensional sinusoidal pore (0.40nm×0.59nm) with a ten-membered ring opening within the layer, and the other set is an interlayer twelve-membered ring supercage structure (0.71nm×1.82nm) (the twelve-membered ring bowl-shaped holes (0.71nm×0.71nm) on the outer surface of the crystal can be regarded as part of the supercage). Based on the unique pore system and acid properties of MCM-22, it has become an important catalytic material in the field of petrochemicals, and is used in alkylation reactions represented by the production of ethylbenzene from benzene and ethylene, gasoline catalytic cracking reactions, alkane aromatization reactions, and MTO reactions. MWW structured silica-alumina molecular sieves are used in It is widely used in acid-catalyzed reactions, which has also prompted scientific researchers to try to introduce various heteroatoms into the MWW structure. In particular, with the development of TS-1 catalytic oxidation research, the introduction of heteroatom Ti into the MWW molecular sieve framework has always been one of the focuses of researchers. It is reported that the synthesized Ti-MWW molecular sieve can show excellent catalytic performance in the field of selective oxidation of hydrocarbons, such as cyclohexanone ammoxidation to cyclohexanone oxime CN20051002447.3, propylene epoxidation to propylene oxide (CN200480015961.4, CN201480052333.7, CN201810222684.8) and other reactions. Therefore, it is of great significance to synthesize a high-performance Ti-MWW molecular sieve catalyst.

[0003] At present, the titanium silicon molecular sieve produced by industrial application is mainly based on fixed bed reactor, which requires the catalyst to have a certain size, shape and mechanical strength to avoid the problem that the molecular sieve powder is fine, difficult to recover, easy to lose, and the powder is not suitable for direct loading into large chemical equipment during the reaction process. In order to solve this problem, patent CN112520753A proposes to add alkaline strong auxiliary agents such as sodium hydroxide, sodium carbonate, sodium acetate, etc. during the synthesis process of TS-1 raw powder. This process will significantly improve the mechanical strength of the catalyst during molding. Patent CN103464197B proposes to add inorganic oxides (TiO2, SiO2, Al2O3, ZnO, etc.) during the molding process of TS-1, and then carry out alkali treatment to obtain a catalyst with high mechanical strength. The catalyst also shows excellent catalytic activity, product selectivity and catalytic life in propylene epoxidation reaction. Patent CN112121871A describes that the molded titanium silicon molecular sieve catalyst is hydrothermally treated with a boron-containing aqueous solution to allow the catalyst to undergo a possible "recrystallization / recrystallization" process, thereby improving the catalyst mechanical strength. The document Chinese J. Catal, 2021, 42: 1561-1575 discloses a method for preparing an integral titanium zeolite catalyst and its application, which is mainly for the finished Ti-MWW molecular sieve. The dual organic templates TMAdaOH and HMI are used for the gas phase crystallization of the Ti-MWW molecular sieve. The mechanical strength of the optimal catalyst listed can reach 23.8 N / cm.

[0004] At the same time, in the field of molecular sieves, the regulation of molecular sieve acid properties is an important factor affecting catalyst performance. In the field of silicon-aluminum molecular sieves, increasing the Al content of the framework can give silicon-aluminum molecular sieves higher acid density and acid strength, while appropriately reducing the Al content can improve the selectivity of the catalytic reaction and the thermal stability of the molecular sieve. The acid strength of ZSM-5 molecular sieves can be modified by the silane selective cracking (SCS) method, thereby effectively regulating the selectivity of 1-C6= cracking to generate C2= and C3=. In the field of silicon-tin molecular sieves, Beta molecular sieves with high Sn content are synthesized by using the all-silicon ITQ-1 molecular sieve crystal transformation strategy or structural rearrangement method, which shows high conversion rate and selectivity in the Baeyer-Villiger (BV) oxidation reaction of cyclohexanone and diadamantanone; in the field of titanium-silicon molecular sieves, the regulation of the acid properties of the Ti active center is also an important means to affect its catalytic reaction activity. The introduction of F into the Ti-MWW molecular sieve can significantly increase the Lewis acid strength of the catalyst, thereby improving the reaction activity, selectivity and stability of the catalyst during fixed bed operation.

[0005] In summary, although the above technologies can effectively improve some properties of Ti-containing zeolite catalysts individually, they are still difficult to meet the actual industrial fixed bed operation requirements. Therefore, it is necessary to develop a suitable, easy-to-control and industrially applicable method to prepare MWW structured titanium-containing zeolite catalysts with high acid strength, high crystallinity and high mechanical strength. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a MWW structured titanium silicon molecular sieve and a preparation method thereof. The MWW structured titanium silicon molecular sieve obtained by the preparation method of the present invention has high acid strength, high crystallinity and high mechanical strength, and exhibits excellent catalytic performance in the epoxidation reaction of linear olefins.

[0007] In a first aspect, the present invention provides a MWW structured titanium silicalite molecular sieve, wherein the mechanical strength of the MWW structured titanium silicalite molecular sieve is 70N / cm-120N / cm, for example, 80N / cm, 90N / cm, 100N / cm or 110N / cm.

[0008] In some embodiments, the silicon-titanium molar ratio Si / Ti of the MWW structured titanium silicon molecular sieve is 40-150. In some embodiments, the silicon-boron molar ratio of the shaped titanium silicon molecular sieve is 200-500.

[0009] In some embodiments, the relative crystallinity of the MWW structured titanium silicalite is 110%-130%, for example, 115%, 120% or 125%.

[0010] In some embodiments, in the pyridine infrared test spectrum of the MWW structured silicon titanium molecular sieve, 1445 cm -1 ±3cm -1 The characteristic peaks in the range of 1880cm -1 ±3cm -1 The peak area ratio of the characteristic peaks in the range is 0.55-0.75, for example, 0.57, 0.6, 0.63, 0.65, 0.67, 0.7 or 0.73.

[0011] In a second aspect, the present invention provides a method for preparing a MWW structured titanium silicon molecular sieve, comprising:

[0012] S1: Pre-treating the raw powder of silicon-titanium molecular sieve with MWW structure with an acid solution to obtain a pre-treated product;

[0013] S2: forming the pretreated product to obtain a formed product;

[0014] S3: mixing the formed product with an organic amine solution and then performing a crystallization treatment.

[0015] In the present invention, the silicon titanium molecular sieve raw powder refers to the molecular sieve powder that has been crystallized and dried but not calcined in the hydrothermal synthesis method.

[0016] The present invention pre-treats the original powder of the silicon-titanium molecular sieve of the MWW structure by using an acid solution. On the one hand, the boron atoms in the original powder of the Ti-MWW molecular sieve can be effectively removed, so that more defective groups are exposed, which is beneficial to its combination with the binder during the molding process, thereby improving the mechanical strength of the subsequent molded molecular sieve. On the other hand, the acid solution treatment can also improve the Lewis acid strength, thereby improving the reaction activity and selectivity of the molded titanium silicon molecular sieve as a catalyst and its stability during the fixed bed operation. In addition, since the defective groups in the molding process will affect the adsorption, desorption and diffusion process of the substrate / product, the present invention further crystallizes the product after the molding treatment in an organic amine solution, and can also effectively improve its crystallinity and further improve the mechanical strength of the molded molecular sieve.

[0017] In some embodiments, in S1, the mass ratio of the silicon-titanium molecular sieve raw powder to the acid solution is 1:(20-55). In some embodiments, the mass ratio of the silicon-titanium molecular sieve raw powder to the acid solution is 1:23, 1:25, 1:29, 1:32, 1:34, 1:36, 1:38, 1:41, 1:43, 1:45, 1:47, 1:49, 1:51, 1:53 or any value therebetween. In some embodiments, the mass ratio of the silicon-titanium molecular sieve raw powder to the acid solution is 1:(30-40).

[0018] In some embodiments, the acid solution is selected from an aqueous solution of an acid. In some embodiments, the acid is selected from at least one of phosphoric acid, hydrochloric acid, nitric acid, sulfuric acid, acetic acid and ethylenediaminetetraacetic acid.

[0019] In some embodiments, the concentration of the acid solution is 0.1 mol / L-2.5 mol / L, for example, 0.3 mol / L, 0.5 mol / L, 1.0 mol / L, 1.3 mol / L, 1.5 mol / L, 1.7 mol / L, 2.0 mol / L or 2.3 mol / L.

[0020] In some embodiments, in S1, the pretreatment includes sequentially subjecting the mixed solution of the silicon titanium molecular sieve raw powder and the acid solution to heat treatment and filtration treatment.

[0021] In some embodiments, after the heat treatment is completed, filtering treatment is directly performed.

[0022] In some embodiments, the heat treatment temperature is 80°C-140°C, such as 100°C, 110°C or 130°C. In some embodiments, the heat treatment temperature is 90°C-120°C.

[0023] In some embodiments, the heat treatment time is 1 h-5 h, for example, 1 h, 2 h, 3 h or 4 h.

[0024] In some embodiments, in S2, the molding process is a molding process conventionally used in the art, such as the molding processes disclosed in CN112354557A, CN112520753A, and CN107511174A.

[0025] In some embodiments, in S2, the molding process includes mixing the pretreated product, an alkaline solution such as alkaline silica sol and a binder such as field sesbania powder to obtain a viscous solid mixture, treating the viscous solid mixture by extrusion molding, spray granulation, ball molding or tablet molding, and then drying and roasting the treated material.

[0026] In some embodiments, in S3, the organic amine solution is selected from an aqueous solution of an organic amine. In some embodiments, the molar ratio of the molded product to the organic amine is 1:(0.1-2.5). In some embodiments, the molar ratio of the molded product to the organic amine is 1:0.5, 1:0.7, 1:0.9, 1:1.1, 1:1.3, 1:1.5, 1:1.7, 1:1.9, 1:2.1, 1:2.3 or any value therebetween. In some embodiments, the molar ratio of the molded product to the organic amine is 1:(0.8-2.0).

[0027] In some embodiments, the mass ratio of the molded product to the water is 1:(10-25), for example, 1:12, 1:14, 1:16, 1:18, 1:20 or 1:22.

[0028] In some embodiments, the organic amine is selected from at least one of piperidine, piperazine, hexamethyleneimine, cyclohexylamine, 1-adamantanamine, N,N,N-trimethyl-1-adamantanammonium hydroxide and methyl orange.

[0029] In some embodiments, the temperature of the crystallization treatment is 120° C.-200° C., for example, 140° C., 160° C. or 180° C. In some embodiments, the time of the crystallization treatment is 5 h-24 h.

[0030] In a third aspect, the present invention provides the use of the shaped titanium silicalite of the first aspect or the shaped titanium silicalite prepared by the preparation method of the second aspect in the epoxidation reaction of olefins such as linear olefins.

[0031] In some embodiments, the reaction comprises reacting a linear olefin with hydrogen peroxide in the presence of a shaped titanium silicalite, wherein the mass of the shaped titanium silicalite is 10%-20% of the mass of the linear olefin, for example, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18% or 19%.

[0032] In some embodiments, the linear olefin is at least one of propylene, 1-butene, 1-pentene, 1-hexene, and 1-octene, preferably 1-hexene.

[0033] In some embodiments, the epoxidation reaction temperature is 40° C.-80° C., the reaction pressure is 0.1 MPa-3 MPa, and the reaction time is 0.5 h-2 h.

[0034] In some embodiments, the raw materials for the reaction include linear olefins, hydrogen peroxide, and a solvent, preferably acetonitrile. In some embodiments, the molar ratio of linear olefins to hydrogen peroxide in the mixed system of the reaction raw materials is 1:1.0-1.5. In some embodiments, the amount of the solvent added is 5 to 10 times the mass of the linear olefin compound.

[0035] Compared with the prior art, the present invention has the following significant advantages:

[0036] 1. The operation is simple and convenient, and the process is easy to control and repeat.

[0037] 2. The Ti-MWW molecular sieve prepared by this method has high acid strength, high crystallinity, and greatly improved mechanical strength, which can meet the requirements of the catalyst for transportation, filling and use in actual industrial production.

[0038] 3. The Ti-MWW molecular sieve exhibits excellent catalytic performance in the epoxidation reaction of linear olefins, that is, the molecular sieve catalyst has high catalytic reaction activity and high selectivity for the target product. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 XRD diagrams of the Ti-MWW molecular sieve in the prior art, the Ti-MWW molecular sieve in Examples 1-2 and Comparative Examples 1-2.

[0040] Figure 2 It is the pyridine infrared spectra of the Ti-MWW molecular sieve in the prior art, the Ti-MWW molecular sieve in Example 1-2 and the Ti-MWW molecular sieve in Comparative Example 1-2. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.

[0042] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0043] The present invention will be described in detail below through examples.

[0044] Unless otherwise specified, all operations in the Examples and Comparative Examples were carried out at room temperature.

[0045] In the present invention, the Ti-MWW molecular sieve in each example is prepared with reference to the method disclosed in the reference (J.Phys.Chem, B 2001,105,2897-2905), wherein the Ti-MWW molecular sieve used in Examples 1 to 9 and Comparative Examples 1 to 2 is a molecular sieve raw powder (not calcined), and the Ti-MWW molecular sieve used in Comparative Example 3 is a molecular sieve activated powder (calcined).

[0046] Conventional Ti-MWW catalyst was prepared according to the public document Chinese J. Catal, 2021, 42: 1561-1575.

[0047] In the present invention, the contents of elements B and Ti in the molecular sieve are analyzed and determined by plasma atomic emission spectrometry (Thermo IRIS Intrepid II).

[0048] The relative crystallinity of the molecular sieve is analyzed by Shimadzu XRD 6000 X-ray powder diffractometer. The ratio of the sum of the peak areas of the five characteristic peaks of 2Theta at 7.3°, 8.1°, 10.2°, 25.2° and 26.3° in the XRD spectrum of each molecular sieve to the sum of the corresponding characteristic peak areas of conventional Ti-MWW is the relative crystallinity of the sample. The larger the value, the better the crystallinity. The relative crystallinity of conventional Ti-MWW catalyst is 100%.

[0049] The mechanical strength of the catalyst was measured using a DL III particle strength tester produced by Dalian Chemical Research and Design Institute. The larger the value, the higher the mechanical strength.

[0050] In the present invention, the acid strength of Ti-MWW molecular sieve is analyzed and determined by referring to the method disclosed in the literature (Catal. Sci. Technol., 2020, 10, 2905-2915), and the wave number of the sample in the Fourier infrared spectrum is 1445cm -1 Peak area / wave number at 1880 cm -1 The trend of the ratio of the peak area at the wave number indicates the acidity of the molecular sieve. The larger the ratio, the stronger the acid strength.

[0051] Example 1

[0052] Step (1): pre-treat Ti-MWW molecular sieve powder with hydrochloric acid solution, wherein the concentration of the hydrochloric acid solution is 1.0 mol / L, and the molecular sieve (dry basis): hydrochloric acid solution is added in a ratio of 1:35 (mass ratio), and stirred at room temperature for 0.5 hour until mixed. Heat to 100° C. and reflux for 2 hours, then filter while hot to obtain Ti-MWW-AC.

[0053] Step (2): Under mechanical stirring, 70g Ti-MWW-AC molecular sieve, 75g alkaline silica sol (40wt%), and 5g sesbania powder are added to a mortar in sequence and mixed evenly. 35g deionized water is added to the above mixture 5 times, and kneaded while stirring to obtain a viscous fixed mixture. Subsequently, the above viscous solid mixture is added to an extruder and mechanically extruded into a round bar with a cross-sectional size of 0.10 cm, placed in an oven for drying for 12 hours, and then transferred to a muffle furnace and heated to 550°C for calcination for 8 hours, and finally a formed sample Ti-MWW-formed is obtained.

[0054] Step (3): 10 g of the Ti-MWW-formed sample obtained in step (2), 14 g of piperidine (wherein the molar ratio of the Ti-MWW-formed sample to piperidine is 1:1.0), and 100 g of deionized water are mixed evenly, stirred at room temperature for 0.5 hours, and then the reaction kettle is transferred, the temperature is raised to 170° C., and the dynamic treatment is performed for 12 hours. Subsequently, the solid product is filtered and washed, and the solid product is dried in an oven for 12 hours to obtain the final catalyst Ti-MWW-1.

[0055] The silicon-titanium molar ratio Si / Ti of Ti-MWW-1 molecular sieve is 40, and the silicon-boron molar ratio Si / B is 2.15.

[0056] The XRD spectrum of Ti-MWW-1 molecular sieve test is as follows Figure 1, its relative crystallinity is 115%. The relative crystallinity of conventional Ti-MWW is 100%.

[0057] The infrared spectrum of Ti-MWW-1 test is as follows Figure 2 , 1445cm -1 / 1880cm -1 The peak area ratio of the characteristic peak of conventional Ti-MWW is 0.62. -1 / 1880cm -1 The peak area ratio of the characteristic peaks is 0.53.

[0058] The mechanical strength of Ti-MWW-1 molecular sieve tested is 80N / cm, and the mechanical strength of conventional Ti-MWW is 25N / cm.

[0059] Comparative Example 1

[0060] The preparation steps were the same as those in Example 1, except that the treatment in step (1) in Example 1 was not performed during the preparation. The obtained molecular sieve was denoted as Ti-MWW-2.

[0061] The silicon-titanium molar ratio Si / Ti of Ti-MWW-2 molecular sieve is 25, and the silicon-boron molar ratio Si / B is 42.

[0062] The relative crystallinity of Ti-MWW-2 molecular sieve was 105%, and the infrared spectrum was as follows: Figure 2 , 445cm -1 / 1880cm -1 The peak area ratio of the characteristic peaks is 0.28.

[0063] The mechanical strength of Ti-MWW-2 tested is 35N / cm.

[0064] Example 2

[0065] Except for the following differences, the remaining steps are the same as in Example 1:

[0066] The concentration of the hydrochloric acid aqueous solution in step (1) is 1.0 mol / L, and the molecular sieve (dry basis): hydrochloric acid solution is 1:40 (mass ratio).

[0067] In step (3), the ratio of titanium silicalite to deionized water is 1:15 (weight ratio), and the ratio of titanium silicalite to HMI (hexamethyleneimine) is 1:1.0 (molar ratio).

[0068] The obtained molecular sieve is recorded as Ti-MWW-3, and the silicon-titanium molar ratio Si / Ti of the Ti-MWW-3 molecular sieve is 60, and the silicon-boron molar ratio Si / B is 250.

[0069] The relative crystallinity of Ti-MWW-3 molecular sieve was 120%. The infrared spectrum was as follows: Figure 2 , 1445cm -1 / 1880cm -1 The peak area ratio of the characteristic peaks is 0.64.

[0070] The mechanical strength of Ti-MWW-3 tested is 100N / cm.

[0071] Comparative Example 2

[0072] The preparation steps were the same as those in Example 2, except that the treatment in step (3) in Example 2 was not performed during the preparation. The obtained molecular sieve was denoted as Ti-MWW-4.

[0073] The silicon-titanium molar ratio Si / Ti of Ti-MWW-4 molecular sieve is 55, and the silicon-boron molar ratio Si / B is 2.12.

[0074] The relative crystallinity of Ti-MWW-4 was 98%, and the infrared spectrum was as follows: Figure 2 , 1445cm -1 / 1880cm -1 The peak area ratio of the characteristic peaks is 0.54.

[0075] The mechanical strength of Ti-MWW-4 tested is 40N / cm.

[0076] Example 3

[0077] Except for the following differences, the remaining steps are the same as in Example 1:

[0078] The concentration of the hydrochloric acid aqueous solution in step (1) is 2.0 mol / L, the molecular sieve (dry basis): hydrochloric acid solution is 1:15 (mass ratio), and the obtained molecular sieve is recorded as Ti-MWW-5.

[0079] Example 4

[0080] Except for the following differences, the remaining steps are the same as in Example 1:

[0081] The concentration of the hydrochloric acid aqueous solution in step (1) is 2.0 mol / L, the molecular sieve (dry basis): hydrochloric acid solution is 1:25 (mass ratio), and the obtained molecular sieve is recorded as Ti-MWW-6.

[0082] Example 5

[0083] Except for the following differences, the remaining steps are the same as in Example 1:

[0084] The concentration of the hydrochloric acid aqueous solution in step (1) is 2.0 mol / L, the molecular sieve (dry basis): hydrochloric acid solution is 1:45 (mass ratio), and the obtained molecular sieve is recorded as Ti-MWW-7.

[0085] Example 6

[0086] Except for the following differences, the remaining steps are the same as in Example 1:

[0087] Step (3) titanium silicate molecular sieve: piperidine = 1:0.8 (molar ratio), the obtained molecular sieve is recorded as Ti-MWW-8.

[0088] Example 7

[0089] Except for the following differences, the remaining steps are the same as in Example 1:

[0090] Step (3) titanium silicate molecular sieve: piperidine = 1:1.2 (molar ratio), the obtained molecular sieve is recorded as Ti-MWW-9.

[0091] Example 8

[0092] Except for the following differences, the remaining steps are the same as in Example 1:

[0093] Step (3) titanium silicalite molecular sieve: piperidine = 1:1.4 (molar ratio), the obtained molecular sieve is recorded as Ti-MWW-10.

[0094] Example 9

[0095] Except for the following differences, the remaining steps are the same as in Example 1:

[0096] Step (3) titanium silicalite molecular sieve: piperidine = 1:1.6 (molar ratio), the obtained molecular sieve is recorded as Ti-MWW-11.

[0097] Comparative Example 3

[0098] Except for using calcined Ti-MWW molecular sieve activated powder instead of Ti-MWW molecular sieve original powder, the rest is the same as Example 1, and the obtained molecular sieve is recorded as Ti-MWW-12.

[0099] The relative crystallinity of Ti-MWW-12 molecular sieve is 108% and the mechanical strength is 15N / cm. -1 / 1880cm -1 The peak area ratio of the characteristic peaks is 0.54.

[0100] Test Case

[0101] The epoxidation reaction of the straight-chain olefin n-hexene was used to evaluate the catalytic activity and selectivity of the conventional Ti-MWW catalyst and the molecular sieves prepared in the embodiments and comparative examples. The reaction process of this embodiment includes: using acetonitrile as a solvent and 31% by mass hydrogen peroxide as an oxidant, adding Ti-MWW molecular sieve, solvent, n-hexene and oxidant into the reaction tube in sequence, and reacting at 0.15MPa and 60°C for 2h. The amount of molecular sieve added is 17% of the mass of n-hexene; the amount of acetonitrile added is 9 times the mass of n-hexene. The molar ratio of n-hexene:H2O2 in the raw material is 1.0:1.0. The specific reaction results are shown in Table 1.

[0102] Table 1

[0103]

[0104] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. MWW structured titanium silicon molecular sieve, in which: The mechanical strength of the MWW structured titanium silicon molecular sieve is 70N / cm-120N / cm; Preferably, the relative crystallinity of the MWW structured titanium silicon molecular sieve is 110%-130%; Preferably, in the pyridine infrared test spectrum of the MWW structured silicon titanium molecular sieve, 1445 cm -1 ±3cm -1 The characteristic peaks in the range of 1880cm -1 ±3cm -1 The peak area ratio of the characteristic peaks in the range is 0.55-0.

75.

2. A method for preparing a MWW structured titanium silicon molecular sieve, comprising: S1: Pre-treating the raw powder of silicon-titanium molecular sieve with MWW structure with an acid solution to obtain a pre-treated product; S2: forming the pretreated product to obtain a formed product; S3: The formed product is mixed with an organic amine solution and then subjected to a crystallization treatment.

3. The preparation method according to claim 2, characterized in that: In S1, the mass ratio of the silicon titanium molecular sieve raw powder to the acid solution is 1:(20-55), preferably 1:(30-40).

4. The preparation method according to claim 2 or 3, characterized in that: The acid solution is selected from an aqueous solution of an acid, and the acid is selected from at least one of phosphoric acid, hydrochloric acid, nitric acid, sulfuric acid, acetic acid and ethylenediaminetetraacetic acid. Preferably, the concentration of the acid solution is 0.1 mol / L-2.5 mol / L.

5. The preparation method according to any one of claims 2 to 4, characterized in that: In S1, the pretreatment includes sequentially subjecting the mixed solution of the silicon titanium molecular sieve raw powder and the acid solution to heat treatment and filtration treatment. Preferably, the filtration treatment is directly performed after the heat treatment.

6. The preparation method according to claim 5, characterized in that: The temperature of the heat treatment is 80°C-140°C, preferably 90°C-120°C; and / or the time of the heat treatment is 1h-5h.

7. The preparation method according to any one of claims 2 to 6, characterized in that: In S3, the organic amine solution is selected from an aqueous solution of an organic amine. Preferably, the molar ratio of the molded product to the organic amine is 1:(0.1-2.5), preferably 1:(0.8-2.0), and the mass ratio of the molded product to the water is 1:(10-25).

8. The preparation method according to any one of claims 2 to 7, characterized in that: The organic amine is selected from at least one of piperidine, piperazine, hexamethyleneimine, cyclohexylamine, 1-adamantanamine, N,N,N-trimethyl-1-adamantanyl ammonium hydroxide and methyl orange; and / or The temperature of the crystallization treatment is 120° C.-200° C., and the time of the crystallization treatment is 5 h-24 h.

9. Use of the MWW structured titanium silicon molecular sieve prepared according to the preparation method of claim 1 or any one of claims 2 to 8 in olefin epoxidation reaction.

10. The use according to claim 9, characterized in that: The reaction comprises reacting a linear olefin with hydrogen peroxide in the presence of a MWW structured titanium silicalite molecular sieve, wherein the mass of the MWW structured titanium silicalite molecular sieve is 10%-20% of the mass of the linear olefin.

Citation Information

Patent Citations

  • Method for producing 1,2-propylene oxide

    CN100540542C

  • A propylene epoxidation catalyst, its preparation method and application

    CN103464197B

  • Methods for preparing propylene oxide

    CN105813741B

  • Method for preparing binderless MWW structure molecular sieve catalyst

    CN107511174A

  • Synthetic method of epoxide

    CN108530393A